2015
DOI: 10.5194/nhessd-3-4435-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

River flood risk in Jakarta under scenarios of future change

Abstract: Abstract. Given the increasing impacts of flooding in Jakarta, methods for assessing current and future flood risk are required. In this paper, we use the Damagescanner-Jakarta risk model to project changes in future river flood risk under scenarios of climate change, land subsidence, and land use change. We estimate current flood risk at USD 143 million p.a. Combining all future scenarios, we simulate a median increase in risk of +263 % by 2030. The single driver with the largest contribution to that increase… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Nevertheless, most studies agree that groundwater extraction is by far the most important driver for the observed subsidence. Subsidence is driven by three main factors: (1) massive-mostly uncontrolled-groundwater extraction for private and industrial purposes; (2) the natural sediment compaction which is not compensated for due to the interruption of natural sedimentation replenishment; and (3) the substantial compaction loads from buildings and other infrastructure [13]. The detailed quantification of these factors' contribution is difficult and a field for further investigation.…”
Section: Jakarta's Flood Risk: Causes and Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most studies agree that groundwater extraction is by far the most important driver for the observed subsidence. Subsidence is driven by three main factors: (1) massive-mostly uncontrolled-groundwater extraction for private and industrial purposes; (2) the natural sediment compaction which is not compensated for due to the interruption of natural sedimentation replenishment; and (3) the substantial compaction loads from buildings and other infrastructure [13]. The detailed quantification of these factors' contribution is difficult and a field for further investigation.…”
Section: Jakarta's Flood Risk: Causes and Trendsmentioning
confidence: 99%
“…A third factor contributing to Jakarta's flood risk is the fact that many of the rivers and drainage canals are poorly maintained and clogged with waste and sediments [13].…”
Section: Jakarta's Flood Risk: Causes and Trendsmentioning
confidence: 99%
“…Subsidence is driven by three main factors: (1) massive -mostly uncontrolled -groundwater extraction for private and industrial purposes, (2) the natural sediment compaction which is not compensated for due to the lack interruption of natural sedimentation replenishment, and (3) the substantial compaction loads from buildings and other infrastructure (Budiyono et al 2016). The detailed quantification of these factors' contribution is difficult and a field for further investigation.…”
Section: Jakarta's Flood Risk: Causes and Trendsmentioning
confidence: 99%
“…A third factor contributing to Jakarta's flood risk is the fact that many of the rivers and drainage canals are poorly maintained and clogged with waste and sediments (Budiyono et al 2016).…”
Section: Jakarta's Flood Risk: Causes and Trendsmentioning
confidence: 99%
“…Beside the tidal flood as the impact of the sea level rise, Jakarta also got a regular flood. A regular major flood happened in 2002, 2007, 2013, and 2014 cause billion dollars loss and created massive indirect economic failure (Budiyono, Aerts, Tollenaar, & Ward, 2016). Without any action, it is predicted that Jakarta will be sinking about 1.8m by 2030 (Jevrejeva, Jackson, Riva, Grinsteed, & Moore, 2016).…”
Section: Introductionmentioning
confidence: 99%